Answer:
Im not a 100% sure but my best guess would be the 3rd equation:
f(x) = (x - 1) (x + 3)
Please let me know if I was wrong, but i hope this helped you!
Answer:
(11, ∞).
Step-by-step explanation:
3 (x+2)+9<6(x-3)
3x + 6 + 9 < 6x - 18
-3x < -18 - 6 - 9
-3x < -33
x > 11 (Note the inequality flips as we are dividing by a negative value).
Answer:
24
Step-by-step explanation:
(72/-9) / (-1/3)
72/-9) x (-3/1)
(72)*(-3) = - 216/ -9
= 24
Answer:
{y,x} = {7,-1}
Step-by-step explanation:
(-7x) + 3x = 4
- 4x = 4
4x = - 4
x = - 1
y = -7x
x = -1
y = -7(-1) = 7
Answer:
X = 4, 3
Step-by-step explanation:
I don't know if that's what you were looking for